Penyuluhan Tentang Pentingnya Optimalisasi Aspek Perkembangan Anak Usia Dini Pada Taman Kanak-Kanak Islam Terpadu Harvysah - Armanila; Nurhikmah Pohan; Susanti Nirmalasari; Reni Khairani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Early childhood is a child who is in the age range of 0-6 years who experiences very rapid development, so it is important to optimize the development aspects of early childhood in order to prepare themselves for the next level. The method used in this counseling is participatory-based counseling involving discussion, simulation, and direct practice. The results of this counseling show that the counseling has succeeded in increasing participants' understanding of the concept of the importance of optimizing aspects of early childhood development, as well as skills in stimulating the physical motor, language, social emotional, religious moral and cognitive development of early childhood. A 30% increase in the pre-test and post-test results shows that this counseling is very effective in improving participants' knowledge and skills. In addition, statistical analysis using the paired sample t-test shows that the difference between the pre-test and post-test scores is significant (p <0.05), which further strengthens the conclusion that the workshop has a positive impact on participants' skills.